Implementation Of Nutrition Program Management On Changes In Stunting Rates In Tambrauw Regency - Rumabar , Marthen Luther Zadrach; Hasmi, Hasmi; Anggai, Martapina; Irab, Semuel Piter; Tingginehe, Rosmin Mariati; Togodly, Arius (Formosa Journal of Science and Technology, 2024)
Stunting is still a global national and regional problem. This study aims to determine the implementation of nutrition management on stunting rates in Tambrauw Regency. This research is qualitative and uses a case study approach. The informants of 25 people were taken by purposive sampling. Data was collected through in-depth interviews and document reviews. The study results found that the implementation of nutrition program management on stunting rates in Tambrauw Regency based on the input elements in terms of quantity and quality, money, and method is still lacking; while the material has been sufficient. Aspects of the management function, and planning have been running, but do not involve the nutrition staff of the health center; Organizing and controlling are not carried out according to operational instructions. The output of the implementation of nutrition programs on stunting rates is still far from the national target.